2003
DOI: 10.1254/jphs.91.305
|View full text |Cite
|
Sign up to set email alerts
|

Effect of TTC-909 on Cerebral Infarction Following Permanent Occlusion of the Middle Cerebral Artery in Stroke Prone Spontaneously Hypertensive Rats

Abstract: Abstract. We investigated the effect of TTC-909, a drug preparation of the stable prostaglandin I 2 analogue clinprost (isocarbacyclin methylester; methyl 5-{(1S,5S,6R,7R)-7-hydroxy-6-[(E)-(S)-3-hydroxy-1-octenyl] bicyclo[3.3.0]oct-2-en-3-yl} pentanoate) incorporated into lipid microspheres, on cerebral infarction 7 days after permanent occlusion of the middle cerebral artery (MCA) in stroke prone spontaneously hypertensive rats (SHRSP). Under the anesthesia, the MCA was permanently occluded above the rhinal f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
0

Year Published

2004
2004
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 25 publications
(22 reference statements)
1
8
0
Order By: Relevance
“…The data imply a protective role for the IP receptor in delayed pyramidal neuron cell death. Our findings in C57Bl/6 male mice are also consistent with those of other studies showing that relatively selective IP receptor agonists reduce delayed neuronal loss in gerbil and rat (Awad et al, 1983; Dohi, 1987; Karasawa et al, 2002, 2003; Takamatsu et al, 2002). However, affinity and selectivity of pharmacological analogs to the G-protein-coupled receptors are often limiting factors for optimal interpretation of the experimental results (Narumiya et al, 1999).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…The data imply a protective role for the IP receptor in delayed pyramidal neuron cell death. Our findings in C57Bl/6 male mice are also consistent with those of other studies showing that relatively selective IP receptor agonists reduce delayed neuronal loss in gerbil and rat (Awad et al, 1983; Dohi, 1987; Karasawa et al, 2002, 2003; Takamatsu et al, 2002). However, affinity and selectivity of pharmacological analogs to the G-protein-coupled receptors are often limiting factors for optimal interpretation of the experimental results (Narumiya et al, 1999).…”
Section: Discussionsupporting
confidence: 93%
“…However, numerous studies have demonstrated that PGI 2 analogs reduce memory impairment in rodents with cerebral embolism, suggesting a role for the IP receptor in modulation of neurological impairment (Awad et al, 1983; Dohi, 1987; Karasawa et al, 2002, 2003; Takamatsu et al, 2002). Researchers have observed that PGI 2 analogs provide neuronal protection and improve the outcome of learning and memory defects in the cerebral ischemia models of focal as well as global ischemia (Awad et al, 1983; Dohi, 1987; Karasawa et al, 2002, 2003; Takamatsu et al, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…PGI 2 IP receptor deficient (IP −/− ) mice displayed exacerbated neuronal death following brain ischemia 2, 3 . In addition, PGI 2 analogs significantly reduced ischemic brain injury 2, 46 . However, the use of PGI 2 and known analogs have limited therapeutic value due to chemical instability, rapid metabolism (t½~ 4 min) 1 , as well as lack of selectivity for the IP receptor resulting in unsafe side effects 7 .…”
Section: Introductionmentioning
confidence: 92%
“…For example, 48 hours following fluid percussion brain injury in rats, PGI 2 treatment reversed blood flow reductions in the injured cortex of rats [13], indicating an improvement in cortical perfusion. Additionally, administration of PGI 2 agonists TTC-909 [14] and ONO-1301 [15] both reduce infarct volume after middle cerebral artery occlusion (MCAO) in rats, with ONO-1301 reducing neurological deficits. TTC-909 was also shown to reduce memory impairments in rats with cerebral embolism [16], supporting the notion that PGI 2 may play a role in cognitive functions.…”
Section: Introductionmentioning
confidence: 99%